If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2 + 6x = -4x + 68 Reorder the terms: -2 + 6x = 68 + -4x Solving -2 + 6x = 68 + -4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4x' to each side of the equation. -2 + 6x + 4x = 68 + -4x + 4x Combine like terms: 6x + 4x = 10x -2 + 10x = 68 + -4x + 4x Combine like terms: -4x + 4x = 0 -2 + 10x = 68 + 0 -2 + 10x = 68 Add '2' to each side of the equation. -2 + 2 + 10x = 68 + 2 Combine like terms: -2 + 2 = 0 0 + 10x = 68 + 2 10x = 68 + 2 Combine like terms: 68 + 2 = 70 10x = 70 Divide each side by '10'. x = 7 Simplifying x = 7
| 0.25x+0.375x=5 | | 12-4=k/6 | | -2n+2-4n=-10 | | -8+3x=-4+9x | | r-87=146 | | 2y=-2x+9 | | 3x-8=9x-4 | | 4.4(n-5)+(-3n)=18 | | 5(-5x+6)=-70 | | 0n+1-4n=-11 | | .25x-5=.75-12 | | 4=7+x+6Xv | | ln(3x+4)=5.25 | | -4n-4+2n=-12 | | 5t^2+30t+100=0 | | 4a-5=3+2a | | (3x-8)=(9X-4) | | 6x-9=(2x-3) | | 4z/10-9=2 | | y=4x+5x-4 | | .75x-5=.75x-12 | | -4x+8=x+3 | | 7s-3s=8 | | -2+3(6-x)=7 | | d^4-18d^2+81=0 | | 8(4-2x)=4(3-2x)+4x | | -5a+3a=-6 | | 9x^-1/x | | d^2-18d^2+81=0 | | 2a+4b-7= | | 44m^2-1=0 | | 4x+5=6-9 |